The complete chloroplast genome sequence of Begonia coptidifolia - Wang, Zheng-Feng (Mitochondrial DNA B Resour, 2021)
Begonia (Begoniaceae) is a large, pantropically distributed genus, comprising more than 1900 species. Due to poorly available genome resources, the phylogeny of this species-rich genus is still challenged. B. coptidifolia is a newly discovered species of restricted distribution in Southern China, and its genetic relationship with the other Begonia species has not been reported. Therefore, in this study, we report for the first time its chloroplast genome for future phylogenetic analysis. The circular chloroplast genome of B. coptidifolia is 169,412 bp in length, with a GC content of 35.57%. Its large single-copy region is 75,937 bp, a small single-copy region is 18,362 bp, and two inverted repeat regions are 37,556 bp and 37,557 bp, respectively. The genome encodes 82 protein-coding genes, 8 ribosomal RNA genes, and 40 transfer RNA genes. Phylogenetic analysis indicated that B. coptidifolia is genetically closest to B. pulchrifolia.